2003
DOI: 10.1068/b12940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accessibility Impacts of Land-Use Scenarios: The Implications of Job Competition, Land-Use, and Infrastructure Developments for the Netherlands

Abstract: Activity-based accessibility measures, describing the level of access to spatially distributed activities, are not put to the same use in land use and/or transport policy evaluations as are infrastructure-based accessibility measures, which describe congestion levels or the average speed on the motorway network. In this paper we attempt to improve the current evaluation practice by the application of potential, activity-based, accessibility measures for the analysis of job accessibility, using existing traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(32 citation statements)
references
References 19 publications
0
27
1
4
Order By: Relevance
“…For the Netherlands, Geurs and Ritsema van Eck, study the effect of transport infrastructure (further subdivided into changes in infrastructure and changes in congestion) and the land use component (measured as the number of jobs), as well as impacts from the interaction of both components [18]. Authors found a higher overall accessibility increase due to changes in employment levels, a lower positive contribution of infrastructure expansion and a negative contribution of the congestion and interaction components.…”
Section: Accessibility Dimensions and Their Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Netherlands, Geurs and Ritsema van Eck, study the effect of transport infrastructure (further subdivided into changes in infrastructure and changes in congestion) and the land use component (measured as the number of jobs), as well as impacts from the interaction of both components [18]. Authors found a higher overall accessibility increase due to changes in employment levels, a lower positive contribution of infrastructure expansion and a negative contribution of the congestion and interaction components.…”
Section: Accessibility Dimensions and Their Decompositionmentioning
confidence: 99%
“…Similarly, in Finland, improvements in road and rail networks between 1970 and 2007 were associated with positive accessibility changes and population growth [16]. Other applications can be found in the field of charging policies, [17], or in the field of congestion impacts, [18]; both generally entailing a negative impact on accessibility due to an increase in transport costs. Also, regarding the transport dimension, some studies found spatial spillover effects, defined as accessibility impacts related with transport infrastructure changes in neighbouring regions ( [19,20]).…”
Section: Accessibility Dimensions and Their Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es importante comprender la accesibilidad como una necesidad primaria (Halden, 2011) no percibida, ya que por medio de ésta se pueden explicar las posibilidades existentes para llegar a diversas actividades como el empleo, conociéndose análisis en Holanda (Geurs y Ritsema, 2003), Alemania (Patuelli, et al, 2007;Reggiani, et al, 2010;Reggiani, et al, 2011), entre otros; así mismo, a nivel urbano, se conocen algunas investigaciones que se han ejecutado con el fin de conocer la cobertura que ofrecen algunos NAP, de forma agregada o por separado, como los nodos de actividad salud (Oppong y Hodgson, 1994;Tanser et al, 2006;Xia et al, 2008;Muñoz y Kallestal, 2012) y educativos (Pacione, 1989;Apparicio y Séguin, 2006;Foley y Pang, 2006;Younes et al, 2016). Vale la pena resaltar que el concepto se ha aplicado en variados campos de estudio, como: desarrollo económico regional (Rietveld y Nijkamp, 1993;Vickerman et al, 1999;Mackinnion et al, 2008), demografía (Kotavaara, 2011), cohesión social (López et al, 2008), sostenibilidad (Vega, 2011;Escobar et al, 2015a), turismo (Kastenholz et al, 2012), contaminación (Escobar et al, 2016), localización de servicios (Park, 2012;Higgs, 2013;), operatividad de modos de transporte (Botero et al, 2011;Escobar et al, 2012, Escobar et al, 2015b, entre otras.…”
Section: Introductionunclassified
“…Previous studies have conducted accessibility analysis to examine how people's access to jobs by car or public transport can be affected by future transport and land-use scenarios (Anderson et al, 2013;Geurs & va Eck, 2003;Tilahun & Fan, 2014). Some studies have also focused specifically on different scenarios of alternative public transport projects, looking at their accessibility impacts across racial/ethnic and income groups (El-Geneidy et al, 2011;Farber & Grandez, 2017;Manaugh & El-Geneidy, 2012;Niehaus et al, 2016).…”
Section: Transportation Equity and Accessibilitymentioning
confidence: 99%